Vibration Monitoring and Analysis of Conveyor Driving Unit of a Coal Transporter - Laksana Guntur, Harus; Krisnahadi, Yanuar (IPTEK The Journal for Technology and Science, 2017)
This paper presents the result of vibration monitoring, simulation and the analysis of conveyor driving unit of a coal transporter. In steam power plant, coal transporter is on of the fundamental equiptment for coal handling and energy supply. Conveyor driving unit (CDU) is the unit in a coal tranporter which drive the conveyor and transport coal from the stockpile/coal yard to the burner. CDU failure cause instability in coal handling process and influence the production capacity of the power plant. To maintain the reliability of the coal transporter, vibration based condition monitoring is conducted. The vibration of CDU is affected by the tranported load, luffing angle and conveying rate. In this paper, the report is focused on the vibration monitoring result and analysis of the influence of the luffing angle and conveying rate (transported load) to the vibration.The CDU is mathematically modeled and its vibration is simulated. Here, conveyor belt tension at driver pulley is assumed to be the main source of vibration,which has frequency of 1.237Hz. Measurement results show that maximum amplitude occurs at frequency of 24.5 Hz, which is closed to the driving motor of the conveyor. The simulation results show that bigger luffing angle and conveying rate increase the vibration amplitude, specifically at horizontal (x) direction.